Prevalence and associated factors of lipohypertrophy in insulin-injected patients with diabetes in selected primary care clinics in Peninsular Malaysian: a cross-sectional study - Alias, Siti Hawa; Teng, Cheong Lieng; Devaraj, Navin Kumar; Amirrudin, Saadatunnoor; Abd Latib, Noor Rawaida; Chong, Fui Yee; Yussof, Syamimi; Mohamad Din, Mohamad Danial; Lim, Poon Wah (Academy of Family Physicians of Malaysia, 2023)
Introduction: This study aimed to determine the prevalence and associated factors of lipohypertrophy in insulin-injecting patients with diabetes at selected primary care clinics in Malaysia. Methods: This cross-sectional study was conducted among adults aged ≥18 years with type 1 or 2 diabetes treated with insulin for at least 6 months at six selected public primary care clinics in Malaysia. The Injection Technique Questionnaire was used, and physical examination was conducted to detect the presence of lipohypertrophy. Univariate and multivariate logistic regression analyses were conducted using IBM SPSS version 26. Results: A total of 506 patients with type 2 diabetes were included in this study; of them, 60.47% were women, and 48.42% were Malays. The prevalence of lipohypertrophy was 39.6% (95% Confidence Interval, CI =35%–44%). The univariate analysis revealed that a larger number of injections per day, longer needle length, repeated use of needles, incorrect rotation of the injection site, longer insulin use duration, higher total insulin dose and higher HbA1c level were significantly associated with lipohypertrophy. In the multivariate logistic regression analysis, incorrect rotation of the injection site was the only independent associated factor of lipohypertrophy. Conclusion: The prevalence of lipohypertrophy in this study is comparable with that in other studies. The identified associated factors of lipohypertrophy must be addressed in ongoing health education for insulin-injecting patients at Malaysian primary care clinics. Educating healthcare professionals and increasing awareness among patients with diabetes are important steps in preventing this complication.